2018
DOI: 10.1016/j.jacc.2018.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Intake and Cardiac Remodeling

Abstract: After 20 years of follow-up, alcohol intake was associated with adverse cardiac remodeling, although it was not related with LV systolic dysfunction in this initially healthy young cohort. Our results also suggest that drinking predominantly wine associates with less deleterious findings in cardiac structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
(36 reference statements)
0
29
1
Order By: Relevance
“…Further, we observed a trend towards an association between increasing amounts of alcohol consumption with a higher risk of incident LV systolic dysfunction (LVEF 50%) (P-for-trend 0.058), and with a higher risk of a clinically relevant decrease in LVEF (!10%) during follow-up (P-for-trend 0.012). Our findings are in contrast with the findings of a previous longitudinal population-based study, that reported no associations between alcohol consumption, LVEF and LV systolic dysfunction [10]. This study was composed of young adults, whereas our study is composed of older adults.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Further, we observed a trend towards an association between increasing amounts of alcohol consumption with a higher risk of incident LV systolic dysfunction (LVEF 50%) (P-for-trend 0.058), and with a higher risk of a clinically relevant decrease in LVEF (!10%) during follow-up (P-for-trend 0.012). Our findings are in contrast with the findings of a previous longitudinal population-based study, that reported no associations between alcohol consumption, LVEF and LV systolic dysfunction [10]. This study was composed of young adults, whereas our study is composed of older adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus far, prospective studies that assessed the association of alcohol consumption and echocardiographic measures of cardiac structure and function are scarce [9,10]. These studies observed that higher alcohol consumption was associated with higher left atrial volume (LAV) [9], a measure of diastolic function, or with higher left ventricular mass index (LVMI) [10], a measure of cardiac remodelling, but no associations were observed between alcohol consumption and LVEF [10], a measure of systolic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcoholic cardiomyopathy (ACM) is a specific heart muscle disease caused by chronic alcohol intake. Chronic alcohol intake tends to increase left ventricular mass and left ventricular dilatation and leads to heart failure (Rodrigues et al., ). Although there are multiple mechanisms causing ACM, excessive activation of the RAS is one of the most important mechanisms.…”
mentioning
confidence: 99%
“…A study based on individual‐participant data for nearly 0.6 million consumers showed that even low alcohol consumption was associated with disease risks (Wood et al., ). Alcoholic cardiomyopathy (ACM) is characterized by myocardial degeneration caused by long‐term drinking, which causes the ventricle to dilate, and manifests as cardiac dysfunction (Iacovoni et al., ; Manthey et al., ; Rodrigues et al., ). Approximately one‐half of all cases of dilated cardiomyopathy are reported to be caused by alcohol (George and Figueredo, ; Li et al., ; Weintraub et al., ).…”
mentioning
confidence: 99%